1997
DOI: 10.1089/hum.1997.8.6-765
|View full text |Cite
|
Sign up to set email alerts
|

A Concentrated and Stable Aerosol Formulation of Cationic Lipid:DNA Complexes Giving High-Level Gene Expression in Mouse Lung

Abstract: Advances in gene therapy vectors and techniques hold promise for treatment of many inherited and acquired diseases. For lung indications, especially those involving the epithelium, delivery of the gene therapy vehicle ideally will involve the use of an aerosol. Aerosol delivery of transgenes using cationic lipids is currently limited by the ability to generate highly concentrated formulations of lipid:DNA complexes that are stable and retain their activity following aerosolization. We have examined many of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 11 publications
2
67
0
Order By: Relevance
“…We studied cationic, non-pegylated (DOTAP:DOPE) and pegylated (GL67) lipoplexes, respectively ( Figure 1). As GL67-based lipoplexes lacking DMPE-pEG 5000 , were not available, 14 we investigated cationic DOTAP:DOPE lipoplexes as a model for lipoplexes without pEG. Cationic lipoplexes based on DOTAP have also been used in a clinical trial for CF gene therapy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We studied cationic, non-pegylated (DOTAP:DOPE) and pegylated (GL67) lipoplexes, respectively ( Figure 1). As GL67-based lipoplexes lacking DMPE-pEG 5000 , were not available, 14 we investigated cationic DOTAP:DOPE lipoplexes as a model for lipoplexes without pEG. Cationic lipoplexes based on DOTAP have also been used in a clinical trial for CF gene therapy.…”
Section: Resultsmentioning
confidence: 99%
“…This fulfills the initial purpose for inclusion of DMPEpEG 5000 , which was to minimize the precipitation of the lipoplexes when they were prepared at high concentrations. 14 Nonetheless, 4 h after preparation a small amount of the GL67 lipoplexes did precipitate.…”
Section: Characteristics Of the Lipoplexes In The Absence Of Cf Mucusmentioning
confidence: 97%
See 1 more Smart Citation
“…27 Confocal microscopy studies revealed that lipoplexes, but not polyplexes, aggregated in the lumen of bronchi and co-localized either totally (DOTAP) or partially (GL-67A) with the surfactant protein A. GL-67A was chosen since it was shown to be a more efficient lipid formulation than Gene Therapy other commercial lipids, such as DOTAP, for mouse and human lung transfection. 9,28 It includes a neutral lipid, DOPE, and a polyethylene glycol-containing lipid, DMPE-PEG5000, which stabilizes the bilayer configuration. It could be possible that these adjunctive components might have influenced the interaction with surfactant.…”
Section: Figure 5 Immunohistochemical Detection Of Gfp Transgene Exprmentioning
confidence: 99%
“…[1][2][3][4] Considering only nonviral DNA delivering agents, several previous works have achieved gene transfer with cationic lipids (lipofection) and polymers (polyfection) to the lungs of laboratory animals by either direct instillation in the nose and trachea [5][6][7] or via the aerosol administration. 8,9 Systemic intravenous infusion of cationic vector/DNA complexes has been attempted and shown to transfect preferentially the lung tissue. 7,[10][11][12][13] The most important determinants for cationic lipid-mediated gene transfer through intravenous administration are the cationic lipid structure, the charge ratio (+/−) between the cationic vector and DNA, [14][15][16] slightly positive PEI complexes as compared with DNA alone, whereas cationic lipid-based vectors, DOTAP and GL-67A, gave not significant luciferase activity.…”
Section: Introductionmentioning
confidence: 99%